Dairy goats, feeding and nutrition [ feeding and nutrition - Cannas, Antonello; Francesconi, Ana Helena Dias (CABI, 2007)
Examining various aspects of dairy goat feeding and nutrition, this book represents a review of scientific research and techniques. It discusses aspects such as the modelling and production of goat's milk as well as the estimation of nutrient requiremets and food intake of goats.